2017
DOI: 10.1016/j.bpj.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Homodimeric Kinesin-2 KIF3CC Promotes Microtubule Dynamics

Abstract: KIF3C is one subunit of the functional microtubule-based kinesin-2 KIF3AC motor, an anterograde cargo transporter in neurons. However, KIF3C has also been implicated as an injury-specific kinesin that is a key regulator of axonal growth and regeneration by promoting microtubule dynamics for reorganization at the neuronal growth cone. To test its potential role as a modulator of microtubule dynamics in vitro, an engineered homodimeric KIF3CC was incorporated into a dynamic microtubule assay and examined by tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The KIF3C L11 insert was also implicated in the ability of homodimeric KIF3CC to be targeted to microtubule plus ends and act as a potent catastrophe factor to promote microtubule dynamics. KIF3CC∆L11 lost the ability to promote catastrophe, suggesting that the loop L11 extension, unique to KIF3C is a structural motif required for regulation of microtubule dynamics by KIF3CC (51).…”
Section: Kinesin-2 Subfamilymentioning
confidence: 99%
See 1 more Smart Citation
“…The KIF3C L11 insert was also implicated in the ability of homodimeric KIF3CC to be targeted to microtubule plus ends and act as a potent catastrophe factor to promote microtubule dynamics. KIF3CC∆L11 lost the ability to promote catastrophe, suggesting that the loop L11 extension, unique to KIF3C is a structural motif required for regulation of microtubule dynamics by KIF3CC (51).…”
Section: Kinesin-2 Subfamilymentioning
confidence: 99%
“…KIF3B does not form heterodimers with . Moreover, multiple studies showed that heterodimerization was preferential over homodimer formation (43,46,48,49) although there is evidence for an injury-specific homodimer of KIF3CC in neurons (45,47,50,51).KIF3AB forms a heterotrimeric complex by association with KAP ( Fig. 1, ( 36,[52][53][54]).…”
mentioning
confidence: 99%
“…In addition, KIF3C exhibits a signature motif conserved in mammals, a 25-residue insert in loop L11 of the catalytic motor domain, which is enriched in glycines and serines, and this L11 insert is not present in other kinesins regardless of species (7,(33)(34)(35). The distinctive L11 domain of KIF3C has been implicated in regulating processivity for KIF3AC (35) and microtubule dynamics for homodimeric KIF3CC (36).…”
mentioning
confidence: 99%
“…As referred to above, in C. elegans mechanosensory axons, the kinesin‐13 family member KLP‐7 is downregulated after injury leading to an increased number of dynamic growing microtubules at the injury site (Ghosh‐Roy et al, ). Conversely, in in vitro assays, the kinesin‐2 family member KIF3C was identified as a key regulator of axon regeneration as it acts as an injury‐specific kinesin with microtubule‐destabilizing function (Guzik‐Lendrum et al, ), capable of promoting microtubule catastrophe (Guzik‐Lendrum et al, , Guzik‐Lendrum et al, ). KIF3C depletion in adult neurons leads to an increase in stable and looped microtubules and delayed axon regeneration (Guzik‐Lendrum et al, ).…”
Section: The Local Modulation Of Microtubule Dynamics Is Crucial For mentioning
confidence: 99%